Fundamentals of soil ecology - Coleman, David C., 1938-; Crossley, D. A. (London ; San Diego, CA : AP, 2018)
This book offers a holistic approach to soil biology and ecosytem function, providing students and ecosystem researchers with a greater understanding of the central roles that soils play in ecosystem development and function. The text emphasizes the increasing importanct of soils as the organizing center for all terrestrial ecosystems and provides an overview of theory and practice in soil ecology, both from an ecosytems and evolutionary biology point of view. This new edition is fully updated, including an expanded treatment of microbial ecology and new sections on advances in molecular techniques and climate change research. These updates make this edition an essential resource for researchers and students in soil ecology and microbiology.
1. Historical Overview of Soil Science and the Intersection of Soil and Ecology 2. Primary Production Processes in Soils: Roots and Rhizosphere Associates 3. Secondary Production: Activities and Functions of Heterotrophic Organisms--Microbes 4. Secondary Production: Activities and Functions of Heterotrophic Organisms--The Soil Fauna 5. Decomposition and Nutrient Cycling 6. Soil Foodwebs: Detritivory and Microbivory in Soils 7. Soil Biodiversity and Aboveground-Belowground Linkages 8. Future Developments in Soil Ecology 9. Laboratory and Field Exercises in Soil Ecology
Includes bibliographical references (pages 313-359) and index.
Keywords: Soil ecology; Soil biology